#### Answer

y = 0.6666666667

#### Work Step by Step

Simplifying
6y + 7 = 18y + -1
Reorder the terms:
7 + 6y = 18y + -1
Reorder the terms:
7 + 6y = -1 + 18y
Solving
7 + 6y = -1 + 18y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-18y' to each side of the equation.
7 + 6y + -18y = -1 + 18y + -18y
Combine like terms: 6y + -18y = -12y
7 + -12y = -1 + 18y + -18y
Combine like terms: 18y + -18y = 0
7 + -12y = -1 + 0
7 + -12y = -1
Add '-7' to each side of the equation.
7 + -7 + -12y = -1 + -7
Combine like terms: 7 + -7 = 0
0 + -12y = -1 + -7
-12y = -1 + -7
Combine like terms: -1 + -7 = -8
-12y = -8
Divide each side by '-12'.
y = 0.6666666667
Simplifying
y = 0.6666666667